EXPERIMENTAL STUDY OF THE MECHANICAL BEHAVIOR OF CARBON FIBER FABRICS REINFORCED THERMOPLASTIC AND THERMOSET COMPOSITES MATERIALS (Sciences & Technologie. B, Sciences de l'ingénieur, 2008)
In order to tackle the issues associated with the use of thermosetting resins (storage, difficult reticulation process, handmade draping, irreversible defects), high performance thermoplastic resinsare now being considered for applications in aeronautics. Indeed, it is possible to get thermoplastic based laminates with various shapes in few stages thanks to a thermoforming process. Thus, theirmechanical behavior needs to be investigated. This study aims at comparing the mechanical behavior of two aeronautical laminates submitted to different stress states. The studied composite materialsconsist of two different materials for the matrix : epoxy (thermosetting resin) or PPS (high performance thermoplastic resin). The matrix was reinforced with the same carbon fiber satinfabrics. Beyond the usual tests performed on composite materials to get the elastic properties, singlebolt double lap bolted joint (bearing test) and single-bolt single lap bolted joint tests were carriedout. Such tests are very important for the design of composite laminates usually joined with bolts or rivets for aeronautical applications.